The Correlation between Parenting Patterns and The Incidence of Wasting among Toddlers in Tempurejo Village, Kediri City - Afifah Ulayya; Oktovina Rizky Indrasari (Ficco Public Health Journal, 2025)
Background: Wasting is a nutritional status problem characterized by weight-for-lengeth or weight -for-height, and it can be influenced by various factors, including parenting patterns. This study aims to determine the relationship between parenting patterns and the incidence of wasting in Tempurejo, Kediri. Methods: This study employed a quantitative approach with a cross-sectional design, involving 178 respondents selected through purposive sampling. Results: Frequency of age 12-36 (143), frequency of democratic parenting (94), authoritarian parenting (92), and permissive parenting (96). Democratic (p=0.011), authoritarian (p=0.017), and permissive (p=0.007) parenting styles were associated with wasting. Conclusions: Parenting styles (democratic, authoritarian, and permissive) were significantly correlated with the incidence of wasting among toddlers in Tempurejo Village, Kediri City. These findings highlight the importance of parental understanding, particularly among mothers, in supporting optimal child growth and development.